Digital Innovation Practices and Supporting Mechanisms in Schools - Mikeladze, Madona; Nakashide-Makharadze, Tatia (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Integrating technology in educational systems represents a complex process encompassing three interrelated domains: pedagogy, change management, and technology. Achieving an optimal balance among these components is crucial for creating an effective educational environment. This study presents the results of empirical research conducted in four countries (Estonia, Finland, Norway and Lithuania). The research aimed to identify and analyze digital innovation practices in schools, specifically to reveal the characteristics of digitally innovative schools and examine the supporting mechanisms for digital innovation practices. Although the educational institutions in the studied countries do not fully meet all the criteria of an innovative digital school, the analysis of each country's experience provides valuable information. The research findings will contribute to the process of implementing and developing digital innovations in schools, which, in turn, will enhance the effectiveness of the educational system in the modern technological environment.